AB1098 Obesity and insulin resistance in fibromyalgia patients. (23rd January 2014) - Grembiale, R.D.; Ursini, F.; Bruno, C.; Savarino, F.; Naty, S.
Abstract : Background: Fibromyalgia is a chronic disorder of uncertain etiology characterized by widespread pain and reduced threshold to pressure and other stimuli. Scientific evidences show a relationship between fibromyalgia and obesity. Insulin resistance, a key feature of obesity and metabolic syndrome (MS), is a now well-recognized cardiovascular risk factor. Objectives: Objective of the study was to evaluate insulin resistance in fibromyalgia patients compared with age- and sex- matched healthy women. Methods: For the present study 53 consecutive fibromyalgia female patients referred to the Internal Medicine Unit, University of Catanzaro (Italy) for chronic widespread pain were recruited. Fibromyalgia was diagnosed by a single specialist according to 1990 American College of Rheumatology (ACR) Criteria [1]. For comparison, 50 healthy age- matched female subjects were used. Body mass index (BMI), blood insulin and glucose were measured after overnight fasting. HOMA-IR, a surrogate measure of insulin resistance, was calculated as previously described by Matthews et al. [2] Results: Mean age was 58.3±6.9 for patients and 56.6±7.4 for controls (p>0.05). Patient's BMI and HOMA-IR, an indirect measure of insulin resistance, were significantly higher compared to healthy age- matched controls (p<0.01 and p<0.05 respectively). Conclusions: Fibromyalgia patients have a higher degree of insulin resistance compared to healthy age-matched controls. References: Wolfe, F., et al., The American College of Rheumatology 1990 Criteria for the Classification of Fibromyalgia. Report of the Multicenter Criteria Committee. Arthritis Rheum, 1990; 33(2): p. 160-72. D.R. Matthews, J.P.Hosker. Homeostasis model assessment: insulin resistance and β-cell function from fasting plasma glucose and insulin concentrations in man Diabetologia 1985;28: 412-9 Disclosure of Interest: None Declared